(untitled) - Bennett, Albert B. (Boston, 2007)
The Seventh Edition of Mathematics for Elementary Teachers: A Conceptual Approach continues their innovative, time-tested approach: an emphasis on learning via specific, realistic examples and the extensive use of visual aids, hands-on activities, problem-solving strategies and active classroom participation. Special features in the text ensure that prospective teachers will gain not only a deeper understanding of the mathematical concepts, but also a better sense of the connections between their college math courses and their future teaching experiences, along with helpful ideas for presenting math to their students in a way that will generate interest and enthusiasm.
Keywords: Mathematics,Toán học